Renewable energy and their environmental impacts in the European Union law - Liakopoulos, Dimitris (Pécs journal of international and European law, 2025)
The present work aims to highlight the innovations of the European legislator in the field of renewable energy. The problems of the ongoing environmental crisis, and especially in the war sector, have had as their basis to open the way to new roads through the simplification of bureaucracy of a road of new stages where environmental policy has found ways to improve the life of the European people, face new energy crises in the near future and above all harmonize, integrate energy policy in the European territory as a necessity of the moment.